Comparing the efficacy and safety of direct oral anticoagulants with vitamin K antagonist in patients with atrial fibrillation and chronic kidney disease stages IV and V: systematic review and meta-analysis - E. G. Skorodumova; A. Yu. Suvorov; S. T. Enginoev; M. A. Kercheva; M. A. Grebenuk (Российский кардиологический журнал, 2023)
Aim. This study aims to compare efficacy and safety of direct oral anticoagulants (DOAC) with vitamin K antagonist (VKA) in patients with atrial fibrillation (AF) and chronic kidney disease (CKD) stages IV and V.Material and methods. We systematically searched the PubMed, Google Scholar, Web of Science databases from 1990 to 2022 and included all published studies that compared DOACs with VKA in patients with atrial fibrillation and chronic kidney disease stages IV and V. To search the articles, we used the PICO strategy: Patient, Intervention, Comparison, Outcome of Interest. Data extraction was undertaken by five independent researches, and then a meta-analysis was performed.Results. Out of all, 6 studies were included in the meta-analysis: 3 randomized controlled trials (n=353) and 3 retrospective analyses (n=37470). The efficacy of DOACs was comparable with VKA. In terms of safety, DOACs and VKA also showed no statistical differences: hemorrhagic stroke, major/minor/gastrointestinal bleeding, general mortality.Conclusion. In terms of efficacy and safety, the indicators of DOACs and VKA were generally comparable.